2012
DOI: 10.1074/jbc.m111.310987
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Storage and Transport in Cells Are Mediated by Glutathione S-Transferase P1-1 and Multidrug Resistance Protein 1 via Dinitrosyl Iron Complexes

Abstract: Background: Nitrogen monoxide (NO) can target intracellular iron pools, leading to dinitrosyl iron complexes (DNICs). Results: NO storage and transport are mediated by glutathione S-transferase P1-1 (GST P1-1) and multidrug resistance protein 1 (MRP1), respectively. Conclusion: GST P1-1 and MRP1 form an integrated detoxification unit regulating storage and transport of DNICs. Significance: These results have broad implications for understanding the transport, storage, and signaling roles of NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(113 citation statements)
references
References 37 publications
8
105
0
Order By: Relevance
“…Given the short half-life of uncomplexed NO, and the need for it to be exported to carry out its extracellular functions, mechanisms for NO storage and transport are critical. Thus, Richardson and colleagues (101) have proposed that cells can form dinitrosyl-diglutathionyl-iron ((GS) 2 -Fe-(NO) 2 ) complexes as long-lived NO intermediates and have provided genetic and pharmacological evidence that these complexes can be effluxed from cells by MRP1 (Fig. 2).…”
Section: Gsh and Mrp1-mediated Transportmentioning
confidence: 99%
“…Given the short half-life of uncomplexed NO, and the need for it to be exported to carry out its extracellular functions, mechanisms for NO storage and transport are critical. Thus, Richardson and colleagues (101) have proposed that cells can form dinitrosyl-diglutathionyl-iron ((GS) 2 -Fe-(NO) 2 ) complexes as long-lived NO intermediates and have provided genetic and pharmacological evidence that these complexes can be effluxed from cells by MRP1 (Fig. 2).…”
Section: Gsh and Mrp1-mediated Transportmentioning
confidence: 99%
“…More recent studies have shown that NO generated by several different sources, including transfection with iNOS or exposure to two exogenous NO generators (i.e. GSNO or spermine NONOate), leads to iron release from wild-type murine embryonic fibroblasts, but not from murine embryonic fibroblasts from MRP1 knockout mice (37).…”
Section: Ubiquitous Gsh Transporter Mrp1 Mediates Nomediated Iron Andmentioning
confidence: 99%
“…GSH completes the coordination sphere of the NO-iron complex to form a DNIC. DNICs can be bound by GST P1-1 or effluxed out of cells via MRP1 (37,38).…”
Section: Model Of D-glucose-dependent No-mediated Iron Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…GSTP has been found to regulate the activities of a number of biologic pathways, such as c-Jun N-terminal kinase (JNK) and tumor necrosis factor receptor-associated factor 2 (Adler et al, 1999;Wu et al, 2006). Furthermore, evidence suggests that GSTP may catalyze the binding of glutathione to cellular proteins (Sglutathionylation) (Townsend et al, 2009) and facilitate the transport of nitric oxide via dinitrosyl-dithiol-iron complexes (Lok et al, 2012).…”
Section: Introductionmentioning
confidence: 99%